Students' Perspectives on Selecta Capita of Mathematics Online Course on Their Ability to Develop Mathematics Task - Satrio Ardiansyah, Adi; Andi Nugroho, Muhammad; Surya Maulana, Bagus; Setyanti, Kurnia; Disi Prasetya, Berlian (KnE Social Sciences, 2024)
The main problem in implementing online lectures is how to adjust what students expect with the achievement of learning quality. This study examines students’ perspectives on effective lectures on the ability to develop mathematics task. Quantitative descriptive research has been carried out on students of the mathematics education study program Universitas Negeri Semarang who took the Selecta Capita of Mathematics course. The subjects in this study were 101 first-year students in the mathematics education study program at Semarang State University for the 2021/2022 academic year. The data were obtained through questionnaires and analyzed by the descriptive statistics. The data that had been obtained and then tabulated in a table, the average value is searched, and presented in the appropriate graph. The results of the study indicate that the availability of learning modules and videos as learning resources is the most important thing that must be prepared during lectures. Furthermore, several other things such as synchronous lectures, discussions using the WhatsApp Group, the use of the learning management system, group assignments, virtual face-to-face meetings, and project assignments need to be prepared during lectures. These results are needed to be applied on team-based project learning models to develop students’ abilities in developing math tasks. Keywords: students’ perspectives, selecta capita, mathematics online course, mathematics task